Employee training and employee performance at Wiawso College of Education - Dzamefe Rejoice Mawuse (University of Cape Coast, 2024)
The study analysed the influence of effective training on employee performance at Wiawso College of Education. Three objectives were stated in achieving the objectives of the study. The objectives were; to discuss the types of training used at the Wiawso College of Education to develop the capacity of employees; to analyse the perceived level of employee performance of Wiawso College of Education; to analyse the effect of training on performance of employees at the Wiawso College of Education. The study was centered on resource-based theory and human capital theory. With respect to the study’s methodology, the quantitative approach was used. The explanatory research design was employed since the research studied on the causal relationship between training and employee performance. The data collection instruments were questionnaire. The simple random sampling technique was used in selecting a respondent of 159. Descriptive and multiple regression were also used to analyse the objectives of the study. The study found that, the company relies more on-the-job training method in their training process than off the job training. Other training methods were the least training method used. The study also found that, on the job training had a positive and significant effect on employee performance. However, off the job training had a low performance of employees of Wiawson College of Education. Also, the performance of the firm had a positive improvement throughout the time period. The study recommended that the organisation should identify the knowledge and skills required to meet its goals and also take steps to hire qualified trainers with requisite skills to take employees through the training programmes for better understanding.
x,78p:,ill